2022
DOI: 10.3390/foods11131838
|View full text |Cite
|
Sign up to set email alerts
|

Production and Shelf-Life Study of Probiotic Caja (Spondias mombin L.) Pulp Using Bifidobacterium animalis ssp. Lactis B94

Abstract: The highly nutritional caja fruit (Spondias mombin L.) is an accessible source of vitamins and antioxidants that are indispensable for the human diet. The objective of the present work was to study the production of a probiotic caja pulp using Bifidobacterium animalis ssp. lactis B94. Firstly, a kinetic study was performed on the fermentation of the caja pulp with Bifidobacterium animalis ssp. lactis B94 to determine the optimum conditions of the process. Growth kinetics revealed that the ideal time for ending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The oligosaccharides formed in the fermentation process of fruit and vegetable juices can act as bifidus factor to balance the human intestinal flora and play a nutritional role in the human body. Studies have shown that after fermentation of the mixture of citrus juice, apple juice, pear juice and carrot juice by Bifidobacterium, the content of vitamin C, beta-carotene and folate increased by2-, 1.5-, and 2.5-fold, respectively ( Rodrigues et al, 2022 ). Polysaccharides in fruit and vegetable juices are hydrolyzed to produce useful components in the fermentation process, such as oligosaccharides which can be used as bifidus factors for human nutritional and health functions ( Fonteles et al, 2018 ).…”
Section: The Improvement Effect Of Probiotics On Fruit and Vegetable ...mentioning
confidence: 99%
“…The oligosaccharides formed in the fermentation process of fruit and vegetable juices can act as bifidus factor to balance the human intestinal flora and play a nutritional role in the human body. Studies have shown that after fermentation of the mixture of citrus juice, apple juice, pear juice and carrot juice by Bifidobacterium, the content of vitamin C, beta-carotene and folate increased by2-, 1.5-, and 2.5-fold, respectively ( Rodrigues et al, 2022 ). Polysaccharides in fruit and vegetable juices are hydrolyzed to produce useful components in the fermentation process, such as oligosaccharides which can be used as bifidus factors for human nutritional and health functions ( Fonteles et al, 2018 ).…”
Section: The Improvement Effect Of Probiotics On Fruit and Vegetable ...mentioning
confidence: 99%
“…Recently, in our laboratory, it was found that pulp from fruits of the Spondias genus serves as an alternative and satisfactory medium for the development of probiotic foods through fermentation with Bifidobacterium animalis ssp. lactis (Albuquerque et al, 2023; Rodrigues, Albuquerque, Azeved, et al, 2022). Umbu‐cajá pulp ( Spondias spp.)…”
Section: Introductionmentioning
confidence: 99%